Evaluating the Impact of N-Glycan Sequon Removal in the p27 Peptide on RSV F Protein Immunogenicity and Functionality - Lotte Jacobs; Annelies Leemans; Kim Stobbelaar; Axelle Fransen; Paul Cos; Peter Delputte (Viruses)
Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory tract infections in young children, elderly and immunocompromised patients worldwide. The RSV fusion (F) protein, which has 5–6 N-glycosylation sites depending on the strain, is a major target for vaccine development. Two to three of these sites are located in the p27 peptide, which is considered absent in virions. Prior research from our group showed that removing the N-glycan at position 116 (N116) in p27 led to higher neutralizing antibody responses and better protection against RSV. In this study, the effect of single, double and triple N-glycan deletion mutations in F p27 was evaluated. Surprisingly, all mutants exhibited similar expressions and functionality to the wild-type F protein. All F p27 glycomutants induced neutralizing antibodies and lowered lung viral loads after an RSV challenge in a mouse model. Although N-glycans in p27 influence immune responses, their exact role in RSV biology remains unclear. Possibly, these glycans, which are mostly conserved, play a role in other aspects of virus replication and biology.